Relationship Marketing and Customer Retention at Event Organizer Palembang - Wati, Indah; Karo, Pelliyezer Karo; Azizah, Syahna Nur; Morena, Mochammad Rian Ahdian (Journal of Management and Administration Provision, 2023)
This study aims to identify the effect of relationship marketing on customer retention, with the locus being CV MS. The study used a quantitative method with multiple linear regression analysis. The sampling technique used the proportionate stratified random sampling method. Primary data collected through questionnaires to 91 samples. Relationship marketing variables were examined through four dimensions: trust, commitment, communication, and complaint handling. The study results showed that all four relationship marketing variables together influenced customer retention by 52.5 percent. If examined partially, the trust variable is the only variable that significantly influences customer retention. A strong correlation between the trust variable and customer retention also supports this. Thus, the success of building trust in CV MS with government clients is the main factor in fostering long-term relationships with consumers.